The characteristics of points of strong summability of the Fourier - Laplace series for functions from the class $L(S^m)$ in the case of critical indicator - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We announce the result that enables one to determine fairly constructive characteristics of a set of pointsof full measure on a sphere $L(S^m)$ at which the strong means converge to a given function $f(·)$.